Magnetically tailored dielectric behaviour of (1-x)Ba0.98Sm0.02TiO3-xBa0.7Sr0.3Fe12O19 ceramic composites - Kaur Arshdeep; Nindrayog Amritpal Singh; Masih Sajan; Middha Shiffali; Kaur Shubhpreet; Kumar Sunil; Ghosh Rubina; Vishwakarma Prakash Nath; Arya Nisharika; Singh Satvir; Tandon Nitin; Sharma Indu; et al. (Processing and Application of Ceramics)
With the growing need for materials for multifunctional devices, we are studying the behaviour of a composite consisting of titanate ferroelectric phase with strong dielectric properties and ferrites with magnetic properties. Solid-state reaction method was used to prepare Ba1-xSmxTiO3 powders, while Ba1-xSrxFe12O19 powders were synthesized by sol-gel auto combustion method. The selected titanate and M-type hexaferrite powders were used for fabrication of (1-x)Ba0.98Sm0.02TiO3-xBa0.7Sr0.3Fe12O19 composites (x = 0.1, 0.2, 0.3, 0.4, and 0.5) by their mixing, compaction and sintering at 1240°C. Phase formation was investigated by XRD and multivalent state of Fe (Fe2+ and Fe3+) was identified from XPS. Matching the unique properties of these materials with each other will favour numerous application paths. The magnetic, magneto-dielectric and magnetoelectric properties of perovskite/hexaferrite composites were investigated. Magnetoelectric coupling was found in all of the composite samples by the magneto-dielectric investigation. The maximum magneto-dielectric response of ∼37.7% in terms of change in dielectric permittivity in presence of magnetic field was measured for the sample with x = 0.4 at magnetic field of 1.2 T and frequency of 100Hz.